The inventor's secret - Morris, Chad (Morris, Chad. Cragbridge Hall, 2014)
When twins Abby and Derick start junior high at the prestigious academy their grandfather founded, Cragbridge Hall, they discover firsthand the dangers of time travel and must find a way to save their parents, who have been sent to the Titanic the night it sank.